Developing an Ingredient Branding Strategy Applied to Pigmented Rice Commodity - Shafira Wuryandani; Dyah Ismoyowati; Endy Suwondo (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Pigmented rice agroindustry has just started its market development, thus require a branding strategy. It may apply an ingredient branding strategy that can increase brand awareness and equity of pigmented rice by highlighting the ingredients. This paper discussed the developing strategy of pigmented rice products using the Customer-Based Brand Equity Model (CBBE). The brand awareness and loyalty survey was conducted to analyze the pigmented rice brand equity. The survey also explored branding media to increase consumers’ brand equity. The survey captured 261 respondents from various cities in Indonesia. The results of the t-test showed a significant difference between regular and occasional consumers. The CBBE diagnosis indicated that the producer should highlight antioxidants, anthocyanin, and other health benefits through advertising, word of mouth, health-related campaigns, and informative packaging.